The Relationship of Alcohol and Other Drug Use Typologies to Sex Risk Behaviors among Vulnerable Women in Cape Town, South Africa - Wechsberg, Wendee M (2012)
BACKGROUND: Alcohol and other drug (AOD) use remains an important contributing factor to the spread of HIV in South Africa, mainly because of the strong associations found between AOD use and sex risk behaviors. Specifically, AOD use can lead to disinhibition and impaired judgment that may result in inconsistent condom use and other risky sex behaviors among vulnerable and disempowered women. METHODS: Latent Class Analysis was used to identify AOD use typologies among 720 vulnerable women from a randomized trial baseline assessment in Cape Town, South Africa and to examine whether these AOD use classes predict sex risk for HIV. RESULTS: Three classes emerged with distinct differences in AOD use: the Marijuana and Alcohol class (34.6%) mainly comprised participants who used marijuana and drank alcohol frequently; the High AOD Risk class (26.1%) mainly comprised participants who used methamphetamine and marijuana, reported heavy drinking, and moderate probabilities of Mandrax use; and the Polydrug use class (39.3%) predominately comprised participants who used methamphetamine, marijuana, and Mandrax. Participants in the Marijuana and Alcohol class were less likely to report past-month unprotected sex with their main sex partner compared with participants in the Polydrug Use class. When examining the adjusted model, Black African women were significantly less likely to report past-month unprotected sex with their main sex partner compared with Coloured women. Women who were HIV negative were more likely to report unprotected sex with their main sex partner than women who were HIV positive. CONCLUSION: The fewer substances that women used seemed to serve as protective factors against engaging in AOD-impaired sex. This study provides an important contribution to understand the intersection of AOD use and sexual risk for HIV by measuring polydrug use among vulnerable women and its association with sexual risk taking.